Efforts to Improve Learning Outcomes of Badminton Forehand Lob Game Using Problem Base Larning Method - Hulu, Anugrah Christian; Liliana Puspa Sari; Sembiring, Ibrahim (LPPM Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2020)
This study aims to see an increase in the results of badminton forehand lob by the application of the Problem Based Learning Method in class VIII students of SMP Hosana Medan in the 2019/2020 academic year. The subjects in this study were class VIII with 30 students who would be given action in the form of the application of the Problem Based Learning Method towards learning outcomes of badminton Forehand lob. This study uses a classroom action method, which consists of two cycles. Learning badminton forehand strokes was carried out using the Problem Based Learning method and ended by presenting the cycle I test and cycle II test with the research instrument of the badminton forehand lob learning outcome test sheet using a portfolio sheet. After the data is collected and analyzed, the results of the analysis are obtained: (1) from the data on the results of the learning test in Cycle I, it is obtained that 15 people (50%) have reached the level of learning completeness, while 15 people (50%) have not reached the level of learning completeness. The average value of student learning outcomes is 60. (2) from the cycle II learning outcomes test, it was found that 26 people (86%) had reached the level of learning completeness, while 4 people (14%) had not The average student learning outcomes are 74. Based on the results of data analysis, it can be said that through the application of problem-based learning methods, the learning outcomes of badminton forehand lob can be improved in Class VIII students of SMP Hosana Medan in the 2019/2020 academic year.